A clear trade‐off between leaf hydraulic efficiency and safety in an aridland shrub during regrowth. (11th August 2021) - Yao, Guang‐Qian; Nie, Zheng‐Fei; Zeng, Yuan‐Yuan; Waseem, Muhammad; Hasan, Md. Mahadi; Tian, Xue‐Qian; Liao, Zhong‐Qiang; Siddique, Kadambot H. M.; Fang, Xiang‐Wen
Abstract: It has been suggested that a trade‐off between hydraulic efficiency and safety is related to drought adaptation across species. However, whether leaf hydraulic efficiency is sacrificed for safety during woody resprout regrowth after crown removal is not well understood. We measured leaf water potential ( ψ leaf ) at predawn ( ψ pd ) and midday ( ψ mid ), leaf maximum hydraulic conductance ( K leaf‐max ), ψ leaf at induction 50% loss of K leaf‐max ( K leaf P 50 ), leaf area‐specific whole‐plant hydraulic conductance (LSC), leaf vein structure and turgor loss point ( π tlp ) in 1‐ to 13‐year‐old resprouts of the aridland shrub ( Caragana korshinskii ). ψ pd was similar, ψ mid and K leaf P 50 became more negative, and K leaf–max decreased in resprouts with the increasing age; thus, leaf hydraulic efficiency clearly traded off against safety. The difference between ψ mid and K leaf P 50, leaf hydraulic safety margin, increased gradually with increasing resprout age. More negative ψ mid and K leaf P 50 were closely related to decreasing LSC and more negative π tlp, respectively, and the decreasing K leaf‐max arose from the lower minor vein density and the narrower midrib xylem vessels. Our results showed that a clear trade‐off between leaf hydraulic efficiency and safety helps C. korshinskii resprouts adapt to increasing water stress as they approach final size. Abstract : A trade‐off between leaf hydraulic efficiency and safety is proposed to be related to drought adaptation, but it is still under debate. Here, leaf hydraulic efficiency clearly traded off against safety in resprouts of Caragana korshinskii, thus helping resprouts adapt to increasing water stress.